MSMEs Marketing Strategies Through The Use Of Social Media: A Systematic Literature Review - Ariyati, Izza Milenia; Ismawati, Ayu Fitria; Rizqillah, Adika Iftitah; Wulandari, Siti Sri; Susanti, Susanti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This research aims to analyze literature regarding marketing strategies used by MSMEs in 2019-2023, as well as analyze the impact of the use of social media by MSMEs in marketing strategies. This research uses a systematic literature review method. The number of articles found was 54, which matched the criteria and keywords of this research theme. The research results show that Sinta indexes more published articles, publication trends increase yearly, and most research types use a qualitative approach. An effective marketing strategy helps increase sales for MSMEs because it can save production costs, and social media platforms become a resource that can reach consumers widely. MSME marketing strategies via social media in 2019-2023 mostly use Instagram, Facebook, and TikTok. This research can be used as a reference for future research. This research can also be used as a reference for MSME owners in implementing marketing strategies, especially social media, to improve performance through product innovation and creativity in marketing.